Enhancing Leptospirosis Awareness: A Study on Knowledge among Health Undergraduate Students in Pontianak, West Kalimantan - Auliya Az Zahra; Mardhia Mardhia; Mahyarudin Mahyarudin; Delima Fajar Liana (Jurnal Veteriner, 2025)
Leptospirosis is a zoonotic infectious disease caused by the spirochete bacteria Leptospira, with a high risk of transmission in flood-prone areas such as Pontianak, West Kalimantan. Health undergraduate students play a critical role in preventing and managing infectious diseases, including leptospirosis. Hence, sufficient knowledge is necessary. This study aimed to describe the knowledge of health undergraduate students in Pontianak regarding leptospirosis. A descriptive study with a cross-sectional approach was conducted involving 172 respondents selected through proportionate stratified random sampling. Data were collected using an 18-question questionnaire covering definitions, etiology, epidemiology, clinical manifestations, transmission mechanisms and pathogenesis, diagnosis, prevention, and management. The results show that most health undergraduate students at Universitas Tanjungpura, Pontianak had poor knowledge (57.5%), while 35.5% had moderate knowledge, and only 7% demonstrated good knowledge. Electronic media or the internet was the most frequently used source of information (51.74%), followed by lecture materials (44.18%), journals (22.67%), textbooks (14.53%), and printed media (11.04%). This study concludes that the majority of students lack knowledge of leptospirosis. Improving health literacy and access to accurate information, particularly through electronic media, is essential to enhance their understanding of the disease.